Will and politics in Augustine: the constitution of a formal ethical-political paradigm in the Middle Ages - Costa Cerqueira, Marcone (Argumentos - Revista de Filosofia, 2026)
Augustine is considered one of the great promulgators of the Christian tradition in the early Middle Ages; his works became one of the foundations for medieval Christian thought, influencing philosophers and theologians. Our objective in this article is to argue, and demonstrate, that Augustine, in view of his important work, established the bases of a formal ethical-political paradigm, having as pillars: I – his conception of will; II – his political theory of the ‘two cities’; finally, III – the break with the classical model between individual and political body. This ethical-political paradigm highlights the formalism of the autonomy of the will to the detriment of material contingencies. In the political field, this perspective shifts the focus from the concrete needs inherent in political relations, establishing a predominance of the ethical over the political, of the formal over the material. In our itinerary, we will first present the foundations of the will in Augustinian thought, then his political theory based on the conception of ‘two cities’, and finally, we will present how this Augustinian paradigm, predominantly formal, displaces the individual from political materiality to ethical formalism, breaking with the foundations of the classical tradition.